Taxation of Income from Undeclared Sources as an Instrument for Combatting Tax Evasion in Poland - Palczewska , Olga (Studia Oeconomica Posnaniensia, 2016)
Tax evasion is a consequence of the interference of public authorities in the amount of financial resources of individuals . The aim of this article is to present the phenomenon of tax evasion and an assessment of the effectiveness of fiscal control in the area of detection of income that is not reflected in declared resources in Poland in the period between 2006 and 2013. First of all the concept of unrevealed resources will be defined and their causes identified. Next the procedure for calculating and collecting tax from such income will be analyzed. The changes with respect to non-declared sources of taxation planned in Polish tax law will also be discussed. Such changes are the effect of a ruling issued by the Constitutional Tribunal, which considered the cur- rent regulations as unconstitutional. In the next part of the article the effectiveness of fiscal controls with respect to the detection of non-declared income will be analyzed.